Pengaruh Pajak Bumi dan Bangunan (PBB) dan Bea perolehan Hak Atas Tanah dan Bangunan (BPHTB) Pada 19 Kota Dan Kabupaten Provinsi Sumatera Barat Pada Tahun 2018-2020 - Ikbal Jauhari; Muhammad Rivandi (JCA (Jurnal Cendekia Akuntansi), 2022)
Since the enactment of Law No. 29 Year 2009 on Regional Taxes and Retribution which was, PBB and BPHTB was turned into a regional government taxes. The purposes of this study were to determine the effects of PBB and BPHTB on regional taxes and the influence of both collections to the regional taxes of Sumatera Barat. Method of analysis used panel data regression analysis. The results showed that PBB and BPHTB have a positive and significant impact on Regional taxes of Sumatera Barat. This research was expected to give contribution as a problem solving related to PBB and BPHTB problem towards regional taxes and can be used as reference for further research. Keywords: PBB, BPHTB, and Regional Taxes